ALMA reveals molecular cloud N55 in the large magellanic cloud as a site of massive star formation - Neelamkodan, Naslim; Hony, Sacha (The astrophysical journal, 2018)
We present the molecular cloud properties of N55 in the Large Magellanic Cloud using 12CO(1-0) and 13CO(1-0) observations obtained with Atacama Large Millimeter Array. We have done a detailed study of molecular gas properties, to understand how the cloud properties of N55 differ from Galactic clouds. Most CO emission appears clumpy in N55, and molecular cores that have young stellar objects (YSOs) show larger linewidths and masses. The massive clumps are associated with high and intermediate mass YSOs. The clump masses are determined by local thermodynamic equilibrium and virial analysis of the 12CO and 13CO emissions. These mass estimates lead to the conclusion that (a) the clumps are in self-gravitational virial equilibrium, and (b) the 12CO(1-0)-to-H2 conversion factor, , is 6.5 × 1020 cm−2 (K km s−1)−1. This CO-to-H2 conversion factor for N55 clumps is measured at a spatial scale of ∼0.67 pc, which is about two times higher than the value of the Orion cloud at a similar spatial scale. The core mass function of N55 clearly show a turnover below 200 , separating the low-mass end from the high-mass end. The low-mass end of the 12CO mass spectrum is fitted with a power law of index 0.5 ± 0.1, while for 13CO it is fitted with a power law index 0.6 ± 0.2. In the high-mass end, the core mass spectrum is fitted with a power index of 2.0 ± 0.3 for 12CO, and with 2.5 ± 0.4 for 13CO. This power law behavior of the core mass function in N55 is consistent with many Galactic clouds.
Gesehen am 11.12.2019